A Bifunctional Spin Label for Ligand Recognition on Surfaces. Issue 32 (6th July 2017) - Hollas, Michael A.; Webb, Simon J.; Flitsch, Sabine L.; Fielding, Alistair J.
Abstract: In situ monitoring of biomolecular recognition, especially at surfaces, still presents a significant technical challenge. Electron paramagnetic resonance (EPR) of biomolecules spin‐labeled with nitroxides can offer uniquely sensitive and selective insights into these processes, but new spin‐labeling strategies are needed. The synthesis and study of a bromoacrylaldehyde spin label (BASL), which features two attachment points with orthogonal reactivity is reported. The first examples of mannose and biotin ligands coupled to aqueous carboxy‐functionalized gold nanoparticles through a spin label are presented. EPR spectra were obtained for the spin‐labeled ligands both free in solution and attached to nanoparticles. The labels were recognized by the mannose‐binding lectin, Con A, and the biotin‐binding protein avidin‐peroxidase. Binding gave quantifiable changes in the EPR spectra from which binding profiles could be obtained that reflect the strength of binding in each case. Abstract : An easily accessible spin label has been developed as a valuable tool for the integration of an EPR‐sensitive probe into linkers between bioligands and surfaces. Gold nanoparticles were linked through the spin label to bioligands, and CW‐EPR spectroscopy was utilized to monitor recognition of surface‐bound mannose and biotin ligands by concanavalin A and avidin‐peroxidase, respectively.